2015
DOI: 10.1504/ijta.2015.067644
|View full text |Cite
|
Sign up to set email alerts
|

Consumer storytelling of brand archetypal enactments

Abstract: The study here probes the perspective that consumers use certain brands as actors that play roles in the consumers' lives and that help consumers as protagonists to enact roles that give them the feelings of achievement, well-being, and/or emotional excitement. The method enables the uncovering of archetypes as unconscious forces that drive consumers to specific actions implicitly and to a less extent, explicitly. The study employs two techniques: degrees-of-freedom-analysis (DFA) to test whether or not consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…There is theoretical support for associating the three brands to specific archetypes and clusters. Apple is included in the creator archetype and the "stability and control" cluster (Haddad et al, 2015;Muniz and Woodside, 2015); Facebook can be included in the "Regular Guy" archetype and in the "belonging and enjoyment" cluster (Roberts, 2010); and Amazon can be included in the explorer archetype and the "independence and fulfillment" cluster (Mark and Pearson, 2001;Hwang, 2017). For each archetype, it is possible to associate specific sentences and words.…”
Section: Methodology and Field Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…There is theoretical support for associating the three brands to specific archetypes and clusters. Apple is included in the creator archetype and the "stability and control" cluster (Haddad et al, 2015;Muniz and Woodside, 2015); Facebook can be included in the "Regular Guy" archetype and in the "belonging and enjoyment" cluster (Roberts, 2010); and Amazon can be included in the explorer archetype and the "independence and fulfillment" cluster (Mark and Pearson, 2001;Hwang, 2017). For each archetype, it is possible to associate specific sentences and words.…”
Section: Methodology and Field Researchmentioning
confidence: 99%
“…Many brands are representations of "modern myths," containing cognitive elements, emotional elements, and unconscious processes. Brand archetypes and myths are considered allegories that support the construction of brand-consumer relationships (Muniz and Woodside, 2015). In this context, specific brands may play a pivotal role in enabling consumers to achieve the proper pleasures that facilitate an implicit brand recognition and consumer-brand relationships and experiences (Woodside et al, 2008).…”
Section: Brand Personality and Brand Archetypesmentioning
confidence: 99%
“…However, consumers develop a variety of rich relationships with brands and, arguably, boiling down to the two dimensions of warmth and competence forfeits some of that variety and depth (Fournier & Alvarez, 2012; Keller, 2012; MacInnis, 2012). Further, consumer storytelling about brand archetypes can convey the richness and complexity of consumer–brand relationships, in this view (Muniz et al, 2015).…”
Section: Consumer Brand Relationshipsmentioning
confidence: 99%
“…Since then, consumer research scholars have embraced theories and methods from the humanities, and more specifically narratives, to understand consumption (Shankar et al , 2001). Storytelling research has been applied to analyze consumer stories in travel blogs (Martin and Woodside, 2011; Tussyadiah and Fesenmaier, 2007) and to confirm if consumers’ own stories enact a specific archetype and how such enactments occur (Muniz et al , 2015). Other studies have examined storytelling in an advertising context and have shown that narratively structured ads result in positive brand attitudes and behavioral intentions, compared to advertisements without consumer narratives (Escalas, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%